IL-13Rα2 Status Predicts GB-13 (IL13.E13K-PE4E) Efficacy in High-Grade Glioma - Julian S. Rechberger; Kendra A. Porath; Liang Zhang; Cody L. Nesvick; Randy S. Schrecengost; Jann N. Sarkaria; David J. Daniels (MDPI AG, 2022)
High-grade gliomas (HGG) are devastating diseases in children and adults. In the pediatric population, diffuse midline gliomas (DMG) harboring H3K27 alterations are the most aggressive primary malignant brain tumors. With no effective therapies available, children typically succumb to disease within one year of diagnosis. In adults, glioblastoma (GBM) remains largely intractable, with a median survival of approximately 14 months despite standard clinical care of radiation and temozolomide. Therefore, effective therapies for these tumors remain one of the most urgent and unmet needs in modern medicine. Interleukin 13 receptor subunit alpha 2 (IL-13Rα2) is a cell-surface transmembrane protein upregulated in many HGGs, including DMG and adult GBM, posing a potentially promising therapeutic target for these tumors. In this study, we investigated the pharmacological effects of GB-13 (also known as IL13.E13K-PE4E), a novel peptide-toxin conjugate that contains a targeting moiety designed to bind IL-13Rα2 with high specificity and a point-mutant cytotoxic domain derived from Pseudomonas exotoxin A. Glioma cell lines demonstrated a spectrum of IL-13Rα2 expression at both the transcript and protein level. Anti-tumor effects of GB-13 strongly correlated with IL-13Rα2 expression and were reflected in apoptosis induction and decreased cell proliferation in vitro. Direct intratumoral administration of GB-13 via convection-enhanced delivery (CED) significantly decreased tumor burden and resulted in prolonged survival in IL-13Rα2-upregulated orthotopic xenograft models of HGG. In summary, administration of GB-13 demonstrated a promising pharmacological response in HGG models both in vitro and in vivo in a manner strongly associated with IL-13Rα2 expression, underscoring the potential of this IL-13Rα2-targeted therapy in a subset of HGG with increased IL-13Rα2 levels.